THE EFFECT OF GIVING ROSELLA FLOWER BREWING ( HIBISCUS SABDARIFFA ) ON THE MOTHER'S HEMOGLOBIN (HB) LEVELS PREGNANT ANEMIA IN THE WORK AREA OF THE COMMUNITY HEALTH CENTER INPATIENT CARE OF DISTRICT TATAKARYA NORTH LAMPUNG - Puspita, Linda; Surani, Wiwik; Herlina, Nina (Universitas Aisyah Pringsewu, 2025)
Anemia in pregnancy is one of the causes of iron deficiency with an incidence in the Tatakarya Inpatient Health Center of 17.33%, anemia has negative impacts such as miscarriage, premature labor, uterine inertia, prolonged labor and bleeding and shock. Prevention of anemia is recommended to consume 60 mg of iron and 0.25 folic acid equivalent to 200 mg of ferrous sulfate during pregnancy at least 90 tablets, in addition to consuming foods high in iron and vitamin C such as Rosella flowers (Hibiscus sabdariffa) which have a vitamin C content that can play a role in regulating iron absorption. The purpose of the study was to determine the effect of giving rosella flower infusion (Hibiscus sabdariffa) on Hemoglobin (Hb) levels of pregnant women with anemia in the Tatakarya Inpatient Health Center Work Area, North Lampung Regency. Quantitative analytical research type, pre-experimental design with one group pretest-posttest approach. The population in this study were all pregnant women who experienced anemia in Trimester III as many as 15 respondents using accidental sampling technique. The study was conducted in September-October 2024. Data collection used observation sheets. Univariate and bivariate analysis (paired sample t-test). The results of the study showed that the average Hb level in pregnant women before being given rosella flower infusion (hibiscus sabdariffa) on the Hemoglobin (Hb) levels of pregnant women with anemia was 10.2 gr / dl and after being given rosella flower infusion (hibiscus sabdariffa) was 10.9 gr / dl. There is an effect of giving rosella flower infusion (Hibiscus sabdariffa) on the Hemoglobin (Hb) levels of pregnant women with anemia in the Work Area of the Tatakarya Inpatient Health Center, North Lampung Regency (p-value = 0.000). Suggestions for pregnant women can consume rosella flower infusion as an alternative to increase Hb levels during pregnancy Keywords: Pregnant women, rosella flowers, Hb levels